GE_GERICHTE P/12626/2017 vom 11. März 2021 - GE Cour de justice (2021)
LÉSION CORPORELLE SIMPLE;VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;CONCOURS D'INFRACTIONS;RESPONSABILITÉ RESTREINTE(DROIT PÉNAL);EXPERTISE | CP.123; CP.219; CP.292; CP.49; CP.19.al2; CPP.10.al2